Effects of a Health Related Moderate Class - More Knowledge Program on Body Mass Index and Physical Fitness in the Primary Schools Students with Overweight and Obesity, Nanoi District, Nan Province - No-in, Kanlayanee; Khanthayot, Chutinan; Yatan, Jinluck (Journal of Health Science of Thailand, 2019)
The objective of this study was to evaluate the effect of a moderate class – more knowledge (MCMKH) program which targeted health promotion on the body mass index and physical fitness in the primary school students with overweight and obesity. It was conducted as a quasi-experimental research with two-group pre-posttest design. The samples were selected by defined criteria as follows: (1) the experimental group was 34 students with body mass index greater than 23 kg/m2 from the first primary school which applied to participate in the MCMKH project by voluntary, and they were provided with the MCMKH activities for one semester; and (2) the control group, 17 students with body mass index greater than 23 kg/m2 from the 2nd, the 3rd and the 4th primary schools where they were provided with regularity teaching. The research instrument consisted of the experimentation tool - the MCMKH which adopted to the context of the experimental group’s school with teachers and students’ participation, and data collection tools included data record form and equipment for physical and fitness examinations. Data analysis was perform by using descriptive statistics, chi-square, independent t-test and simple linear regression. It was found that, after 3 months of intervention, body mass index of the experimental group was not different from that of the control group. All physical fitness results of the experimental group, except for flexed-arm hang, were statistically significant better changed than the control group. In conclusion, although the MCMKH program did not affect students’ body mass index, it improved students’ physical fitness. This activity should be continued and be assessed in a longer time period.